2022
DOI: 10.1007/s40262-022-01114-5
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Population Pharmacokinetic Analysis for Exploring Ciprofloxacin Pharmacokinetic Variability in Intensive Care Patients

Abstract: Background and Objective Previous pharmacokinetic (PK) studies of ciprofloxacin in intensive care (ICU) patients have shown large differences in estimated PK parameters, suggesting that further investigation is needed for this population. Hence, we performed a pooled population PK analysis of ciprofloxacin after intravenous administration using individual patient data from three studies. Additionally, we studied the PK differences between these studies through a post-hoc analysis. Methods Individual patient da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When comparing our PPK modelling results with those of studies performed in critically ill 21 , 24 , 29 , 30 and burn patients, 31 CL CR was likewise associated with CL of both amoxicillin 29 , 31 and ciprofloxacin. 21 , 24 , 30 The IIV of CL was lower in our study population, suggesting that exposure is more predictable in non-critically ill patients, also in the acute phase of infection. Therefore, the acute phase of infection only had a marginal effect on the pharmacokinetics of the investigated antibiotics in non-critically ill patients.…”
Section: Discussionmentioning
confidence: 74%
“…When comparing our PPK modelling results with those of studies performed in critically ill 21 , 24 , 29 , 30 and burn patients, 31 CL CR was likewise associated with CL of both amoxicillin 29 , 31 and ciprofloxacin. 21 , 24 , 30 The IIV of CL was lower in our study population, suggesting that exposure is more predictable in non-critically ill patients, also in the acute phase of infection. Therefore, the acute phase of infection only had a marginal effect on the pharmacokinetics of the investigated antibiotics in non-critically ill patients.…”
Section: Discussionmentioning
confidence: 74%
“…The mathematical models commonly used in MIPD software, for example, do not always capture the range of pharmacokinetics and pharmacodynamics seen across heterogeneous critically ill populations. Numerous studies have highlighted the difficulty that such models have in accurately predicting the pharmacokinetics in critically ill patients for multiple antibiotics, including vancomycin [5,6], amikacin [4], gentamicin, tobramycin [7], meropenem [8], ciprofloxacin [9], cefotaxime [10], and polymyxin [11]. This problem is exacerbated in critically ill patient groups, such as pediatrics or those undergoing renal replacement therapies, whose pharmacokinetic profiles are distinct from those of more typical patients.…”
Section: Therapeutic Drug Monitoring In the Critically Ill Is Challen...mentioning
confidence: 99%
“…Acute severe inflammation can alter drug exposure [ 1 , 2 ] in patients and thereby potentially impact drug efficacy and toxicity, especially for drugs with narrow therapeutic windows, e.g., antimicrobials [ 3 ] and immunosuppressants [ 4 ]. Studies in critically ill or septic patients, where acute inflammation is often present, show large inter-individual variability [ 5 ] in pharmacokinetics, e.g., clearance and distribution volume [ 6 ]. Several clinical pharmacokinetics studies investigating patient populations suffering from acute inflammation by empirically employing population pharmacokinetics modeling approaches have found that increased levels of inflammatory biomarkers such as C-reactive protein (CRP) or interleukin-6 (IL-6) may contribute to the observed variability in pharmacokinetics [ 7 ].…”
Section: Introductionmentioning
confidence: 99%